2013
DOI: 10.1017/s104161021300149x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant topographical organization in gray matter structural network in late life depression: a graph theoretical analysis

Abstract: Our findings suggest that the gray matter structural networks are not globally but regionally altered in LLD patients. This multivariate structural analysis using graph theory might provide a more appropriate paradigm for understanding complicated neurobiological mechanism of LLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…Using inter-regional correlations of gray matter volumes, another study in LLD also reported higher clustering in addition to longer path length (Ajilore et al., 2014), although no network differences were revealed by the same group in a subsequent analysis of white matter network on the same sample (Charlton et al., 2014). Preserved network organization in LLD has been reported in other studies using gray matter volumes (Lim et al., 2013) and functional data (Bohr et al., 2013). Furthermore, no study has performed a combined analysis of regional cortical thickness and network properties in the same sample, which will allow us to directly investigate the macro-level impact of cortical atrophy beyond the potentially affected regions.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Using inter-regional correlations of gray matter volumes, another study in LLD also reported higher clustering in addition to longer path length (Ajilore et al., 2014), although no network differences were revealed by the same group in a subsequent analysis of white matter network on the same sample (Charlton et al., 2014). Preserved network organization in LLD has been reported in other studies using gray matter volumes (Lim et al., 2013) and functional data (Bohr et al., 2013). Furthermore, no study has performed a combined analysis of regional cortical thickness and network properties in the same sample, which will allow us to directly investigate the macro-level impact of cortical atrophy beyond the potentially affected regions.…”
Section: Introductionsupporting
confidence: 76%
“…To the best of our knowledge, this was the first study to compare regional cortical thickness and network measures in the same sample. Unlike the Voxel-based morphometry (VBM) approach in previous studies (Lim et al., 2013), we used regional cortical thickness to construct our structural covariance networks, thereby overcoming the main limitation of VBM, providing a mixed measure of the cortical gray matter, including surface area, cortical folding, as well as cortical thickness (Hutton et al., 2009). The structural covariance approach also offers another alternative approach that could sidestep the limited validity of DTI-based approaches to map cortico-cortical connectivity due to the multitude of branching and crisscrossing fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic, demographic and host factors play an important role in AD development. Presence of APOE-ɛ4 allele has been associated with increased rate of cognitive decline and increased neuropathology including greater β-amyloid deposition and medial temporal lobe atrophy (Ohm et al, 1995; Dal Forno et al, 1996; Geroldi et al, 1999; Martins et al, 2005; Lim et al, 2013). Higher educational attainment has also been associated with reduced risk of AD in multiple studies (McDowell et al, 2007; Roe et al, 2007; Meng and D’Arcy, 2012) potentially through cognitive reserve mechanism (Stern, 2006; Brayne et al, 2010).…”
Section: Assessing Network-level Changes Associated With Cognitive Trmentioning
confidence: 99%
“…Altered topological properties of functional networks are associated with depression,21 22 and preclinical, prodromal and clinical AD 20 23–25. Recent graph theoretical applications to assess the grey matter structural covariance networks in LLD demonstrated vulnerabilities in the cortical-subcortical topological properties 26 27. Using diffusion tensor imaging, distinct changes in the network efficiency measures were associated with depression severity and remission in those with LLD 28 29.…”
Section: Introductionmentioning
confidence: 99%